Comparing the Accuracy of Silicone and Polyether in Reproducing Gingival Height for Implant Supported Crown: an in vitro study - Derafshi R; Sabouri AA; Kazemeini J (Shiraz University of Medical Sciences, 2015)
Statement of Problem: Accurate impressions are one of the most critical factors in achieving acceptable restorations. When pouring the impressions of implant supported restorations, soft materials like silicone and polyether are used to reconstruct the gingival form around the implants. To the best of our knowledge, no study has been conducted on the comparison of the accuracy of these soft materials. Objectives: To evaluate the accuracy of polyether and silicone in reproducing the correct depth of gingival sulcus around the implants by probing. Materials and Methods: By the use of a periodontal probe, the gingival height was measured in six marked areas of one maxillary partial edentullism model on which two fixture analogs were attached and three points were marked around each analog for measurements, which was considered as an index height. Addition silicone impression material (putty and wash) was used to simultaneously take 10 impressions of the model. The samples were randomly divided into two groups of 5 and each impressions was poured twice; for the first group, the impressions were first poured with silicone, and for the second one they were poured with polyether material for reproducing the gingival contour; in the second group, the procedure was performed in reverse. Therefore, there were 10 casts in each group and because each cast contained two analogues, and each analogue was marked in three points for measuring gingival height, 60 numbers were achieved for each group as the gingival height. The mean gingival heights were compared by paired t-test using SPSS software, version 18 (p = 0.05). Results: Comparison of the mean gingival height of the silicone and control groups revealed that there was no significant difference between the two groups (p = 0.090), whereas, a significant difference was found between the mean gingival height of the polyether and control groups (p = 0.034). Conclusions: Within the limitation of this study, it was concluded that for reproducing the gingival height around the implants, silicone materials are more appropriate than polyether ones.